Berberine activates peroxisome proliferator‐activated receptor gamma to increase atherosclerotic plaque stability in Apoe−/− mice with hyperhomocysteinemia. Issue 6 (15th April 2016) - Li, Hongjun; He, Chengyan; Wang, Jingying; Li, Xiaoou; Yang, Zhaowei; Sun, Xiaoying; Fang, Ling; Liu, Ning
Abstract: Aims/Introduction: An elevated level of plasma homocysteine has long been suspected as a metabolic risk factor for the development of atherosclerotic vascular diseases in diabetes. Berberine (BBR) has several preventive effects on cardiovascular diseases. The effects of BBR on atherosclerotic plaque stability increased by homocysteine thiolactone (HTL) remain unknown. Materials and Methods: The model of atherosclerotic vulnerable plaque was induced by placing a collar around the carotid artery in Apoe −/− mice. Endothelium‐dependent relaxation was assayed by organ chamber. Results: Homocysteine thiolactone (50 mg/kg/day, 8 weeks) reduced the atherosclerotic plaque stability in the carotid artery of Apoe −/− mice, which was reversed by BBR administration (1.0 g/kg/day). In vivo and ex vivo experiments showed that HTL dramatically reduced acetylcholine‐induced endothelium‐dependent relaxation and superoxide dismutase activity, and increased malondialdehyde content, which were inhibited by BBR. Importantly, all effects induced by BBR were abolished by GW9662, an antagonist of peroxisome proliferator‐activated receptor‐γ. Incubation of cultured endothelial cells with HTL significantly reduced cell viabilities and enhanced production of reactive oxygen species. Pretreatment of cells with BBR dose‐dependently reversed HTL‐induced detrimental effects, which were GW9662‐reversible. Conclusions: Berberine increases atherosclerotic plaque stability in hyperhomocysteinemia mice, which is related to the activation of peroxisome proliferator‐activated receptor‐γ and subsequent suppression of oxidative stress in endothelial cells. Abstract : An elevated level of plasma homocysteine has long been suspected as a metabolic risk factor for the development of atherosclerotic vascular diseases in diabetes. We reported that berberine, as a natural production, increase atherosclerotic plaque stability in hyperhomocysteinaemia mice, which is related to the activation of PPARγ and subsequent suppression of oxidative stress in endothelial cells.